1991
DOI: 10.1159/000243390
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Edge Frequency of the EEG in Healthy Neonates and Variation with Behavioural State

Abstract: Spectral edge frequency (SEF) of the EEG was studied in 51 healthy neonates to assess its value as a measure of cerebral maturation. SEF was calculated as the frequency below which 95% of the power in the power spectrum resides. Summated SEF (sSEF) of 4 EEG channels correlated significantly with gestational age (r = 0.83).sSEF varied with behavioural state and with EEG derivation. Intra- and interindividual variability were both greater in preterm compared to term babies. We conclude that SEF is a useful measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 7 publications
1
19
1
Order By: Relevance
“…In contrast to the majority of articles (22,23,27,(32)(33)(34)(35)(36), we studied maturational changes of spectral power analysis quantitatively and automated on whole 4-h recordings, including several sleep-wake cycles. From a previous article using the same subjects, we observed periodic variation in background activity with alternating periods of discontinuity and continuity, suggestive for two to four sleep-wake cycles per 4-h recording (19).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the majority of articles (22,23,27,(32)(33)(34)(35)(36), we studied maturational changes of spectral power analysis quantitatively and automated on whole 4-h recordings, including several sleep-wake cycles. From a previous article using the same subjects, we observed periodic variation in background activity with alternating periods of discontinuity and continuity, suggestive for two to four sleep-wake cycles per 4-h recording (19).…”
Section: Discussionmentioning
confidence: 99%
“…The relative power of a band is the ratio of the absolute power of that band to the total power of all bands and expressed as a percentage. Spectral edge frequency is the frequency that delimits 95% of the total spectral power between 0.5 and 30 Hz (12). Asymmetry was calculated as the ratio of the total absolute power of the recordings from the left side (Fp1, C3, and O1) to the total absolute power of the recordings from the right side (Fp2, C4, and O2).…”
Section: Methodsmentioning
confidence: 99%
“…Bell et al (3) demonstrated a significant negative correlation between the absolute power of the signal below 1 Hz (the ␦ band) and gestational age in 60 infants between 29 and 42 wk gestation. The same authors also reported a significant positive correlation between the spectral edge frequency (the frequency below which 95% of the power resides) between 0.3 and 30 Hz and gestational age in 51 infants between 29 and 41 wk gestation (12). Others have studied sleep patterns and brain maturation using spectral energies in infants between 28 and 32 wk gestation (13)(14)(15).…”
mentioning
confidence: 90%
“…In the fetal baboon, the SEF was demonstrated to be a good discriminator of EEG patterns (8). This EEG parameter was also useful in measuring cerebral maturation in the newborn infant, demonstrating a significant correlation with gestational age (10). This study also demonstrated that the SEF was significantly higher in active sleep compared with quiet sleep.…”
Section: Real-time Spectral Analysis Of the Fetal Eegmentioning
confidence: 53%
“…However, the aEEG employs signal-processing techniques such as band-pass filtering and amplitude and time compression and rectification (26), adequate for screening purposes but insufficient to obtain detailed information regarding amplitude and frequency components embedded in the signal. In contrast, automated scanning of the EEG by spectral analysis as described in this study offers both accuracy and ease of interpretation and, when effectively displayed, provides a sensitive and reliable monitor of cortical activity (5,9,10). The system can also be applied postnatally, so that central neurologic adaptation can be evaluated both in preterm and term newborns.…”
Section: Real-time Spectral Analysis Of the Fetal Eegmentioning
confidence: 99%